AB0618 A unique ultrasound pattern of adipose tissue in systemic sclerosis patients: a comparison with rheumatoid arthritis patients and healthy controls. two sides of adipose tissue involvement in systemic chronic inflammatory diseases. (15th June 2017) - Rotondo, C; Fanizzi, R; Chialà, A; Anelli, MG; Righetti, G; Nivuori, M; Praino, E; Dinoia, L; Lopriore, S; Laselva, G; Scioscia, C; Cacciapaglia, F; et al.
Abstract : Background: Systemic sclerosis (SSc) and rheumatoid arthritis (RA) are both chronic and systemic inflammatory diseases, involving connective tissue. The adipose tissue is acknowledged as an immune organ that secretes numerous inflammatory signals and it is supposed playing an important role in up-regulation of inflammatory status. A few data are published on altered white adipose tissue (WFT) distribution in patients (pts) with RA. None data are available about WFT distribution in SSc pts Objectives: We aimed to characterize the subcutaneous adipose tissue (total (sWFT); superficial (SsWFT); inner (IsWFT)) and visceral adipose tissue (vWTF) thickness, evaluated by ultrasound (US) of abdominal adipose tissue, in SSc pts, with different body mass index classes (BMI), comparing with RA pts and healthy controls (HC). Methods: 42 SSc pts, 57 RA pts and 12 HC were recruited in this study. WFT measurements were assessed, using US (7.5 MHz probe), along the xiphoumbilican line: sWFT thickness (distance between the inner edge of the skin at the outer edge of the alba line (AL)), SsWFT (lobular upper zone of sWFT), IsWFT (sWFT- SsWFT); vWFT thickness (distance between the inner edge of the AL and the peritoneal line). Results: No subject enrolled had metabolic syndrome. RA pts had thicker vWFT (15.6±7.6mm) than SSc pts (10.8±5.8mm) or HC (10.1±3.8mm) (p=0.001). In particular, the upper-weigh RA pts had vWFT 88% thicker than upper-weight HC and the RA obese pts had vWFT 87% thicker than obese HC. While, the upper-weight SSc pts had vWFT 22% thicker than upper-weight HC, and the SSc obese pts had vWFT 16% thicker than obese HC. Positive correlations were found between all WFT measures and BMI in RA pts and HC (p≤0, 05). In SSc pts we found lack of correlation between SsWFT and BMI (r=0.232; p=0.145). Of note, only in SSc pts we observed different US WFT patterns (fig. 1 a, fig. 1 b) characterized by rearrangement of normal sWFT structure (HC fig. 1 c and RA pts fig. 1 d). These structural rearrangements consisted in the absence of adipose lobules, replaced by hypoechoic – anechoic areas (fig.1 a) (attributable to edema), or by hyperechoic lines and spots (fig.1 b) (attributable to fibrotic replacement of subcutaneous abdominal fat), independently by SSc diffuse or SSc limited skin subset. Conclusions: In SSc and RA the WFT is abnormal. The WFT in RA seems be altered just for dimension and distribution, in particular the vWFT is overexpressed; it might be due to vWFT hyperactivity induced by inflammatory status. In SSc, the WFT is altered in the structure of sWFT. A direct involvement of sWFT in pathologic mechanism of SSc is supposed. An edema phase and a fibrotic phase of abdominal sWFT can be hypothesized, independently by skin involvement. If these findings will be confirmed by fat histological analysis, the US of WFT might be an important tool for the clinicians to identified the earlier stage and/or the active phase (edema) of SSc, in order to support physicians in the decision making about the treatment management. Disclosure of Interest: None declared